2010
DOI: 10.1134/s0030400x10060093
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sub-Doppler absorption contour in gas-dynamic beams

Abstract: The formation of the Doppler contour P (D)(?) of absorption lines upon the excitation of particles in the volume of a gas-dynamic beam by light propagating in a direction orthogonal (reduced) to the beam axis is analyzed. Integral representations of P (D)(?) are obtained for arbitrary relations between the nozzle outlet diameter D and the collimating aperture diameter B in the excitation region are obtained. An optimal configuration at which the reduced Doppler contour is the narrowest at a high density of bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Compared with the work of Gabbanini et al, [4] our number is also smaller. However, our data are consistent with the data of Klyucharev and Sepman, [13] considering that the data of Klyucharev and Sepman [13] are for an unresolved fine structure 5𝑝 state. The reason may be due to the fact that the ionizing laser intensity 𝐼 PI , employed by Dinneen et al [2] and Gabbanini et al [4] are not the average intensity 𝐼 PI of the ionization laser seen by the atoms in the MOT as employed in the our work.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Compared with the work of Gabbanini et al, [4] our number is also smaller. However, our data are consistent with the data of Klyucharev and Sepman, [13] considering that the data of Klyucharev and Sepman [13] are for an unresolved fine structure 5𝑝 state. The reason may be due to the fact that the ionizing laser intensity 𝐼 PI , employed by Dinneen et al [2] and Gabbanini et al [4] are not the average intensity 𝐼 PI of the ionization laser seen by the atoms in the MOT as employed in the our work.…”
supporting
confidence: 92%
“…4. Dinneen et al [2] and Gabbanini et al [4] have determined the absolute photoionization cross section for the 5𝑃 3/2 state of 87 Rb using atoms confined in a magneto-optical trap, 𝜎 PI = 13.6 ± 1.2 Mb at 413.1 nm and 𝜎 PI = 12.5 ± 1.1 Mb at 406.7 nm reported by Dinneen et al, [2] and 𝜎 PI = 14.8 ± 2.2 Mb at 476.5 nm reported by Gabbanini et al [4] Klyucharev and Sepman [13] reported 𝜎 PI = 9.8 Mb at 444.0 nm for an unresolved fine structure 5𝑝 state using hot atoms. It seems strange that the present photoionization cross section at 473 nm is smaller than that of Dinneen et al [2] at higher ionizing energy.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Solid lines in Figures 4 and 5 are plotted using Formula (19). Note that the theoretical results well describe the experimental data.…”
Section: Discussion Of the Line-shape Structurementioning
confidence: 67%
“…The second type represents a supersonic beam with v lg ≈ 1100 m/s [15] and a rather specific velocity distribution function [19]. An additional experimental possibility is represented by laser cooled atomic beams [20,21], which are characterized by small v lg around 12 m/s, which corresponds to the sub-thermal temperature interval lying below 1 K and practically negligible transversal velocity.…”
Section: Experimental Setup and Spectroscopic Datamentioning
confidence: 99%